2016
DOI: 10.1017/s1460396916000133
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric evaluation of tandem-based cervical high-dose-rate brachytherapy treatment planning using American Brachytherapy Society 2011 recommendations

Abstract: PurposeThis study evaluated dosimetric parameters for cervical high-dose-rate (HDR) brachytherapy treatment using varying dose prescription methods.MethodsThis study includes 125 tandem-based cervical HDR brachytherapy treatment plans of 25 patients who received HDR brachytherapy. Delineation of high-risk clinical target volumes (HR-CTVs) and organ at risk were done on original computed tomographic images. The dose prescription point was defined as per International Commission in Radiation Units and Measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Onal et al [ 20 ] concluded that CT-based planning in ICBT is superior to conventional planning in target volume coverage and appropriate evaluation of OARs because the conventional plan overestimates tumor doses and underestimates doses to OARs. Goyal et al [ 21 ] found that point A dose prescriptions do not provide consistent coverage of the HR-CTV, and the difference in coverage increases with increasing CTV for conventional and CT image-based dose prescription approaches. In our study, it was evident that the use of CT image-based treatment planning for ICBT provides the scope to delineate the volumes of the target and OARs, generate DVH data, and optimize doses to each of them, which can prove to be a better surrogate for disease response and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Onal et al [ 20 ] concluded that CT-based planning in ICBT is superior to conventional planning in target volume coverage and appropriate evaluation of OARs because the conventional plan overestimates tumor doses and underestimates doses to OARs. Goyal et al [ 21 ] found that point A dose prescriptions do not provide consistent coverage of the HR-CTV, and the difference in coverage increases with increasing CTV for conventional and CT image-based dose prescription approaches. In our study, it was evident that the use of CT image-based treatment planning for ICBT provides the scope to delineate the volumes of the target and OARs, generate DVH data, and optimize doses to each of them, which can prove to be a better surrogate for disease response and toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…V100 describes how closely the intended treatment could be achieved in terms of target coverage, providing information indirectly on the proportion of the underdosed area. For fractionated treatment, however, D90 and V100 are only usable for evaluation after the last fraction, as it uses summed doses of all fractions [9,13]. It was reported that 2D BT planning achieved lower HR-CTV and dosages to organs at risk (OARs) in patients with big cervical tumors than in those with small tumors.…”
Section: Discussionmentioning
confidence: 99%